Technical-and-Economic Efficiency of Draft Enriched with Oxygen in Small-Capacity Heating Boilers - P. Ratnikov; D. Mendelev; I. Trusova; S. Kabishov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2013)
Data on complex experimental and theoretical investigations pertaining to efficiency of oxygen-enriched draft in the small-capacity heating boilers as exemplified by the plant HEIZA (HW-S-10/K) have been presented in the paper. The paper provides a calculation model of heating processes in heat generator burner (as exemplified by HEIZA plant). Simulation of heating processes in the operational zone has been executed in paper. The experimental data have proved model adequacy. The calculation scheme of the plant will be used in future for determination of power and ecological efficiency of draft enrichment with oxygen.